Edible Coating untuk Memperpanjang Umur Simpan Stroberi: Tinjauan Sistematis - Nur Afni; Elya Antariksana Bachmida (Lembaga Pengembangan Kinerja Dosen, 2026)
Strawberries are horticultural commodities that are highly susceptible to postharvest deterioration due to their high respiration rate, microbial activity, and oxidative degradation, resulting in a relatively short shelf life. This study aimed to evaluate the effectiveness of edible coatings in extending strawberry shelf life through a systematic literature review (SLR) approach. Literature was collected from several scientific databases using keywords related to edible coating, shelf life, and strawberry, covering publications from 2019–2026. From an initial 109 articles, a selection process based on inclusion and exclusion criteria resulted in 35 articles specifically discussing the application of edible coatings on strawberries. The synthesis results showed that all studies reported an extension of shelf life after edible coating application, although the effectiveness was influenced by the type of material, formulation, and storage conditions. Chitosan was the most widely used coating material due to its natural antimicrobial activity and excellent film-forming ability. The incorporation of bioactive compounds such as essential oils, plant extracts, and phenolic compounds was proven to enhance antifungal and antioxidant activities. In addition, nanotechnology-based systems demonstrated better preservation performance compared to conventional systems. However, methodological standardization and industrial-scale validation are still required to support commercial implementation.